Celebrating the 55th anniversary of the Journal of Civil Engineering and Management: editor’s introduction - Kaklauskas, Artūras; Zavadskas, Edmundas Kazimieras; Ubartė, Ieva (Journal of Civil Engineering and Management, 2022)
Celebrating the 55th anniversary of the Journal of Civil Engineering and Management: editor’s introduction. Journal of Civil Engineering and Management, 28(1), 1–5.